TRADISI ZIARAH DI MAKAM KIAI AGENG MUHAMMAD BESARI TEGALSARI, PONOROGO, JAWA TIMUR - Saefullah, Asep; Cahyadi, Indrawan (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2023)
ABSTRACT This article describes the pilgrimage tradition at the Tomb of Kyai Ageng Muhammad Besari in Ponorogo, East Java. The article aims to reveal the figure of Kyai Ageng Muhammad Besari and its role in Ponorogo, and the form of rituals and motivations of pilgrims. Further, it explores the aspect of religious tourism of this tomb and how it could be related to the strengthening of national identity. The study employed qualitative design. The data was collected through observation, interviews, and documentation. The study results show that the tradition of pilgrimage of the tomb of Kyai Ageng Muhammad Besar has ritual and social aspects; the motivations of pilgrims are based on: mystical beliefs, worship, appreciation of ulama, and simply grave pilgrimage (ziarah kubur). This study enriches the literature on the religious tourism and socio-religious practice of the local people by visiting the grave of pious figures. Keywords: Pilgrimage Tradition, Religious Tourism, National Identity, Muhammad Besari, Tegalsari. ABSTRAK Artikel ini mengkaji tradisi ziarah Makam Kiai Ageng Muhammad Besari. Tujuannya untuk mengungkap figur Kiai Ageng Muhammad Besari dan peranannya di Ponorogo, bentuk ritual dan motivasi para ziarah. Di samping itu, artikel ini akan mengungkap potensi pengemabangan wisata religi di Makam Kiai Ageng Muhammad Besari, baik situsnya sendiri maupun ekonomi rakyat. Metode yang digunakan adalah kualitatif. Pengambilan data dilakukan dengan cara observasi, wawancara, dan studi dokumentasi. Hasil pembahasan menunjukkan bahwa tradisi ziarah makam Kiai Ageng Muhammad Besar memiliki aspek ritual dan social; motivasi peziarah antara lain karena kepercayaan mistis, ibadah, apresiasi kepada ulama, dan sekadar ziarah kubur. Kata Kunci : Tradisi Ziarah, Wisata Religi, Identitas Nasional, Muhammad Besari, Tegalsari